Penerapan Restorative Justice Dalam Perkara Tindak Pidana Korupsi Sebagai Upaya Pengembalian Kerugian Negara - Ali Habib (Corruptio, 2020)
The Handling of corruption now is indeed more oriented to how to put as many corruptors as possible into a Penitentiary, while corruption itself is still rampant. The deterrent effect which is currently no longer felt by corruption convicts while serving prison sentences and the overflow of prisoners who are no longer sufficient, makes the government move quickly and look for a legal breakthrough related to reducing the level of corruption in Indonesia. The Attorney General's Office of the Republic of Indonesia (RI) as one of the Law Enforcement Officers who have the authority to carry out Corruption Criminal Investigations has issued a Circular Letter for the Deputy Attorney General for Special Crimes (SE Jampidsus) Number: B-765/F/Fd.1/04/2018 dated  April 20 2018 concerning the Technical Guidelines for Handling Corruption Case Investigation Stage, which in essence the Investigation must be strived to find the amount of State Financial Losses, which meant the cooperative attitude of the parties involved to recover the financial losses of the State, it can be taken into consideration as a non-continuation of the legal process which certainly takes into account certain limitations (restorative justice). The problem is how to apply the restorative justice model in an effort to recover state losses. The research results obtained are, the application of restorative justice methods conducted by the Republic of Indonesia's Attorney General's Office can be optimally used in handling corruption cases specifically for the recovery of state finances and future expectations related to handling cases of corruption in Indonesia.